Cutaneous bacillary angiomatosis in the setting of immunosuppression: A rare case in a heart transplant recipient - Chloe Devoy; Régine Mydlarski; Fatemeh Jafarian (SAGE Open Medical Case Reports)
Bacillary angiomatosis is a rare, opportunistic infection caused by Bartonella spp . In the skin, neovascular proliferation results in erythematous and violaceous papules and nodules. While there are many reports of bacillary angiomatosis in solid organ transplant recipients, only two cases are documented in cardiac transplant recipients. Herein, we report a case of bacillary angiomatosis in a 67-year-old male post-orthotopic cardiac transplant who presented with erythematous papules scattered on the chest, back, and extremities. Biopsies revealed lobular capillary proliferation in the superficial dermis and positive Warthin–Starry staining. Nucleic acid amplification by PCR identified Bartonella quintana . After completing a 3-month course of doxycycline 100 mg twice daily, the patient had complete resolution of skin findings. The rise in solid organ transplants, combined with the expanding repertoire of immunosuppressive therapies, has significantly improved patient survival. However, it has also created a favorable environment for opportunistic infections, including bacillary angiomatosis, to emerge as a growing concern.